264 Occupational asthma in New Zealand sawmill workers: A longitudinal study. (11th October 2013) - McLean, D J; Douwes,; Van, Dalen; Demers,; Cheng,; Shanthakumar,; Pearce,
Abstract : Objectives: Wood dust is known to be associated with a range of respiratory effects including reduced lung function, increased bronchial responsiveness and occupational asthma. Cross-sectional studies have suggested an excess of asthma symptoms and lung function decline in sawmill workers. The study aims were to measure the incidence of new-onset asthma, to examine longitudinal changes in lung function, and associations with dust exposures. Methods: Associations between dust exposures, asthma symptoms and lung function were studied over three years in a prospective cohort of sawmill workers. Respiratory morbidity was assessed using spirometry and symptom questionnaires, and personal dust exposure was measured, initially on recruitment into the study and then annually for at least two years. Results: We recruited 281 sawmill workers from seven sawmills. Wood dust sampling (n = 300) showed an overall average of GM = 0.6 mg/m 3 (GSD 3.41), range <0.1 to 16.9 mg/m 3 . Asthma symptoms were more common in workers with high exposure compared to the reference group with low exposures (OR = 1.31, 95% CI = 0.45–3.83). The incidence of new-onset asthma was 4.6% overall, and 8% among those with high "dry"dust exposure. In the longitudinal follow-up of workers a clear decline in forced expiratory volume in 1 second (FEV1 ) and maximal mid expiratory flow (MMEF) was evident in the high exposure group, when compared with the non/low-exposed. Although the numbers were small, the decline over the 3 years in both FEV1 and MMEF was statistically significant in the high exposure group. Conclusions: This study confirms that New Zealand sawmill workers generally experience levels of dust exposure below most exposure standards. Notwithstanding this, there is evidence of an increased risk of developing asthma symptoms and lung function decline (of an obstructive nature) over time even at low dust levels, with a suggestion of a dose-response relationship between dust levels and the development of symptoms.